STATE FORMATION IN CENTRAL AND WEST ASIA DURING THE 10th-13th CENTURIES - Atik, K. (Journal of Oriental Studies, 2022)
During the period beginning form the 10th century until the Mongol conquests, a series of states emerged in Central Asia and West Asia. These states were different from their predecessors, the Abbasid Caliphate and its successor states, as well as from their successors the Mongol Empire and the successor Khanates of the Mongol Empire in the same region in terms of their state formation processes and political structures. As a result, the state structures as well as the political players in the region changed dramatically, and a form of hybridization in state formation and state structures as well as the political systems shaped these regions. The Turkic and other nomadic elements in these regions began converting into Islam at around this time in masses, and their conquests in the settled areas of Central and Western Asia created a new political environment where the nomadic dynasties began to rule over both nomadic and sedentary areas for the first time with dual administrative structures. whereas the nomadic empires of the previous periods were ruling the steppe directly and delegating the administration of the sedentary areas to the vassal kings, the new dynasties began to rule over the cities as well, and in fact began settling in the cities. This paper examines the state formation that resulted in this new environment which became a precursor to the following Mongol era.